Clasificacion de cultivares de tomate mediante el metodo de componentes principales - Fraga Aguiar, N.=700 1 Moya, C.; Alonso, M. del C.
(En, Es)
Ilus., 5 ref.
Keywords: LYCOPERSICON ESCULENTUM; VARIACION GENETICA; GENOTIPOS; FITOMEJORAMIENTO; SLECCION; CUBA